Effect of Post-Processing on the Microstructure of WE43 Magnesium Alloy Fabricated by Laser Powder Directed Energy Deposition - Leila Sorkhi; Nathan J. Madden; Grant A. Crawford (Journal of Manufacturing and Materials Processing)
Additive manufacturing of magnesium (Mg) alloys is of interest for the fabrication of complex-shaped lightweight materials. This study evaluates the microstructure of WE43 Mg alloy deposited using laser powder directed energy deposition (LPDED) additive manufacturing technique in as-deposited and post-processed conditions. As-deposited samples exhibited roughly 2% porosity, which was reduced to below 0.1% after hot isostatic pressing. Despite limited grain growth after heat treatment, some grains experienced abnormal grain growth, likely due to Zener pinning and non-uniform dissolution of grain boundary precipitates. Moreover, as-deposited specimens contained Nd-rich grain boundary precipitates which dissolved during post-processing. Additionally, during heat treatment. a fine distribution of needle-like β1 or β precipitates formed. Overall, the precipitate size and distribution following heat treatment was non-uniform, likely because of the non-uniform response of the LPDED material to heat treatment, owing to the variation in local- and global-temperature profiles during deposition. Furthermore, arc-shaped phases with a high concentration of Y, O, and Zr were present for all processing conditions and are associated with the passivation of the feedstock powder prior to deposition. Moreover, an equiaxed-grain structure with a random orientation and a finer grain size in the regions adjacent to the arc-shaped phases was observed in all processing conditions.